Isolation and validation of antimalarial compounds from Phyllanthus emblica leaves for new antimalarial drug development - Selvam Naveenkumar; Chinnaperumal Kamaraj; Vinoth Kumarasamy; Chidambaram Jayaseelan; Pradisha Prem; Rajagopalan Vijayalakshmi Boomija; S. R. Suseem; Vetriselvan Subramaniyan; Jayanthi Barasarathi; Ling Shing Wong (Scientific Reports)
Abstract Natural products can serve as an alternative source of novel therapies that are required to address the problem of malarial infection resistance. Indian gooseberry (Phyllanthus emblica L.) leaves are often used in traditional medicine to treat fevers, but there isn’t enough scientific proof that they contain antimalarial and effective phytochemicals. This study’s primary goal was to investigate the antimalarial efficacy of P. emblica leaf ethyl acetate extract against Plasmodium falciparum (3D7) and its cytotoxicity against the HeLa cell line. The active compounds from P. emblica were isolated using a bioassay-guided fractionation of column chromatography technique, and NMR spectroscopy was employed to identify their structures. The drug’s anti-malarial efficacy was assessed by estimating its growth-inhibitory activities employing the SYBR Green I asexual parasite drug assay. The cytotoxic effect was evaluated using the MTT assay. P. falciparum dihydroorotate dehydrogenase protein (Pf-DDP) was used as a drug target to investigate molecular docking. P. emblica crude extract and two fractions exhibited > 90% inhibition of 3D7 parasite proliferation, indicating good antimalarial activity at 100 and 10 µg/mL, respectively. Subsequently, the column chromatography study of each fraction, a targeted purification, contributed to the separation of six active compounds designated as 9-hydroxy isolongifolene (C1), Hexadecanoic acid (C2), Phenol, 2,6-Bis(1,1-Dimethylethyl) (C3), Furan, tetrahydro-3-methyl-4-methylene (C4), Octadecanoic acid (C5), and Beta-Sitosterol (C6). Compound C4 showed stronger bioactivity against P. falciparum (3D7) (IC50 4.32 µg/mL) parasites than other constituents, equivalent to the drug-sensitive strains (100 µg/mL). Considering the IC50 levels of the two compounds, 90.56 and > 100 µg/mL, respectively, both demonstrated low cytotoxicity against HeLa cell lines. This research offers scientific support for the historical application of P. emblica in combating malaria. Building on existing knowledge, this study represents a groundbreaking effort to isolate and identify antimalarial compounds from P. emblica leaves for the first time. Moreover, our research underscores the potential of P. emblica in the development of antimalarial agents, encouraging further investigation of different species to suppress the growth of P. falciparum. This plant species could be a valuable source for developing new anti-malarial drugs.